2022
DOI: 10.3390/jcm11216543
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Serum Albumin and Post-Operative Outcomes among Patients Undergoing Common Surgical Procedures: An Analysis of a Multi-Specialty Surgical Cohort from the National Surgical Quality Improvement Program (NSQIP)

Abstract: While studies have demonstrated an association between preoperative hypoalbuminemia and adverse clinical outcomes, the optimal serum albumin threshold for risk-stratification in the broader surgical population remains poorly defined. We sought define the optimal threshold of preoperative serum albumin concentration for risk-stratification of adverse post-operative outcomes. Using the American College of Surgeons National Surgical Quality Improvement Program Database, we identified 842,672 patients that had und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…SA is an important factor used to evaluate patient nutritional status. Hypoalbuminemia indicates nutritional decline in patients with severe disease, and also malnutrition in cancer patients, and is reportedly associated with poor prognoses, increased staging, and reduced OS rates due to malignant tumors ( 25 28 ). Preoperative hypoproteinemia patients have also been shown to have increased tumor spread rates and increased risks from adverse outcomes within 1 month after surgery ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SA is an important factor used to evaluate patient nutritional status. Hypoalbuminemia indicates nutritional decline in patients with severe disease, and also malnutrition in cancer patients, and is reportedly associated with poor prognoses, increased staging, and reduced OS rates due to malignant tumors ( 25 28 ). Preoperative hypoproteinemia patients have also been shown to have increased tumor spread rates and increased risks from adverse outcomes within 1 month after surgery ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoalbuminemia indicates nutritional decline in patients with severe disease, and also malnutrition in cancer patients, and is reportedly associated with poor prognoses, increased staging, and reduced OS rates due to malignant tumors ( 25 28 ). Preoperative hypoproteinemia patients have also been shown to have increased tumor spread rates and increased risks from adverse outcomes within 1 month after surgery ( 25 ). SA levels before treatment are independent prognostic parameters for disease-free and progression-free survival in EC patients ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ideally plasma albumin should be measured before major surgery and for high-risk patients, and repeated after large volumes of intravenous fluids or blood products (examples 1 and 3 in Boxes 1 and 3). For anesthesiologists, knowing preoperative plasma albumin concentration has added value in assessing patient risk due to the strong association between hypoalbuminemia (less than 35 g/l) and postoperative complications and mortality 35,36 due to both malnutrition and chronic disease.…”
Section: Hypoalbuminemiamentioning
confidence: 99%
“…14 Hypoalbuminemia is clearly and closely linked to poor outcomes [15][16][17] particularly in surgical patients. [17][18][19] In the early landmark Veterans' Affairs trial of preoperative feeding of surgical patients before abdominal surgery it was found that only in the severely malnourished patients diagnosed by weight loss and serum albumin levels did benefit in terms of noninfectious outcomes occur 20 from what would now be considered excessive parenteral nutrition therapy. The risks for surgery in hypoalbuminemic patients are substantial extending even to those undergoing metabolic surgery for obesity.…”
mentioning
confidence: 99%
“…In patients who were critically ill with serum albumin levels <2.5 g/dl, some patients did not respond to nutrition support, which was linked to poorer intake of dietary protein, and they had a higher mortality 14 . Hypoalbuminemia is clearly and closely linked to poor outcomes 15‐17 particularly in surgical patients 17‐19 . In the early landmark Veterans’ Affairs trial of preoperative feeding of surgical patients before abdominal surgery it was found that only in the severely malnourished patients diagnosed by weight loss and serum albumin levels did benefit in terms of noninfectious outcomes occur 20 from what would now be considered excessive parenteral nutrition therapy.…”
mentioning
confidence: 99%